Genome‐wide analysis of esophageal adenocarcinoma yields specific copy number aberrations that correlate with prognosis. Issue 4 (21st January 2014) - Frankel, Adam; Armour, Nicola; Nancarrow, Derek; Krause, Lutz; Hayward, Nicholas; Lampe, Guy; Smithers, B. Mark; Barbour, Andrew
<x xml:space="preserve">Abstract</x> The incidence of esophageal adenocarcinoma (EAC) has been increasing rapidly for the past 3 decades in Western (Caucasian) populations. Curative treatment is based around esophagectomy, which has a major impact on quality of life. For those suitable for treatment with curative intent, 5‐year survival is ∼30%. More accurate prognostic tools are therefore needed, and copy number aberrations (CNAs) may offer the ability to act as prospective biomarkers in this regard. We performed a genome‐wide examination of CNAs in 54 samples of EAC using single‐nucleotide polymorphism (SNP) arrays. Our aims were to describe frequent regions of CNA, to define driver CNAs, and to identify CNAs that correlated with survival. Regions of frequent amplification included oncogenes such as EGFR, MYC, KLF12, and ERBB2, while frequently deleted regions included tumor suppressor genes such as CDKN2A/B, PTPRD, FHIT, and SMAD4. The genomic identification of significant targets in cancer (GISTIC) algorithm identified 24 regions of gain and 28 regions of loss that were likely to contain driver changes. We discovered 61 genes in five regions that, when stratified by CNA type (gain or loss), correlated with a statistically significant difference in survival. Pathway analysis of the genes residing in both the GISTIC and prognostic regions showed they were significantly enriched for cancer‐related networks. Finally, we discovered that copy‐neutral loss of heterozygosity is a frequent mechanism of CNA in genes currently targetable by chemotherapy, potentially leading to under‐reporting of cases suitable for such treatment. © 2014 Wiley Periodicals, Inc.